Reply to the Comment Re: Magalhães-Sant’Ana, M. Animals 2019, 9, 168 - Manuel Magalhães-Sant’Ana (Animals, 2020)
I am pleased that my viewpoint on traditional Chinese veterinary acupuncture (TCVA) has caught the attention of researchers from the China Agricultural University [...]